Theoretical Foundations for the Development of Active Organometallic Additives for Polyethylene - Iqbolov, Shohruh; Botirov , Arslonbek; Panjiyev , Bobur (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This article investigates the theoretical and practical foundations of obtaining active organometallic additives for modifying the polyethylene (PE) matrix. The chemical inertness of polyethylene and existing problems regarding the direct attachment of metal centers are analyzed, highlighting the shortcomings of traditional two-stage schemes. To reduce processing stages and ensure strong bonding of the metal to the polymer chain, the research proposes a technology for the direct incorporation of active organometallic compounds during the crosslinking process. Furthermore, physical and chemical crosslinking methods (Daoplast, Engel, Pont a Mousson, UHF) are comparatively examined, and the significance of organometallic (ionic) crosslinks in polymer recyclability is substantiated.